Chemical constituents with chemotaxonomic value from Aconitum georgei Comber. (October 2022) - Yao, Linlin; Yan, Yuanfeng; Shu, Yan; Yang, Yujun; Ce, Guo; Wang, Jiapeng; Yin, Tianpeng; Cai, Le
Abstract: Aconitum georgei Comber is a China-specific Aconitum (Ranunculaceae) plant. In the present study, eighteen compounds, including fourteen diterpenoid alkaloids (1 –14 ) and four nonalkaloidal constituents (15 –18 ) were isolated from the roots of A. georgei . Among them, fifteen compounds (1 –11 and 14 –18 ) have not previously been found in this species, and 3-methoxymethylbenzoate (17 ) has not previously been isolated from the Aconitum genus. The chemotaxonomic value of these compounds was explored through network analysis. The results showed that some of these compounds such as falconeridine (6 ) and 14-anisoyl- N -deethylaconine (10 ) showed limited distribution in the genus, which could help to narrow species identification to A. georgei where other phenotypic characters are limited. Highlights: Eighteen compounds were isolated from Aconitum georgei. Fifteen compounds were isolated in A. georgei for the first time. 3-methoxymethylbenzoate has not previously been isolated from genus Aconitum. Compound-species network analysis exhibited their chemotaxonomic value.